2004
DOI: 10.1039/b315523d
|View full text |Cite
|
Sign up to set email alerts
|

Pyridylpyrrolides as alternatives to cyclometalated phenylpyridine ligands: synthesis and characterization of luminescent zinc and boron pyridylpyrrolide complexes

Abstract: The synthesis, structure, and properties of six luminescent pyridylpyrrolide complexes and the first structural characterization of pyridylpyrrolide metal complexes are reported. A series of new zinc complexes, bis(pyridylpyrrolyl)zinc, (R2PyrPy)2Zn (R = Me, Et, iPr, tBu, and Ph), that vary in their substituents on the pyrrole ring (Me, Et, iPr, tBu, and Ph), were prepared. Pyrrole substitution produced small structural changes in the complexes and affected the fluorescence properties very little. The zinc com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 91 publications
3
43
0
2
Order By: Relevance
“…Like pyridylpyrroles, [8][9][10] they may display not only high electrical conductivity, but also the capability to form complexes of various chemical natures with better electronic and optoelectronic characteristics than uncomplexed polymers. Luminescent complexes of pyridylpyrroles with boron and zinc compounds have thus been proposed as an alternative to cyclometallated phenylpyridine ligands for use in organic light-emitting diode (OLED) materials, [8] while complexes of pyridylpyrroles with alcohols have been thoroughly explored as model compounds (analogous to pyridylindoles) for investigation of the natures of hydrogen bonds in such biologically important objects as DNA and RNA and for study of the mechanism of photoinduced mutagenesis through intermolecular excited state double proton transfer. [9,10] Polypyridines are known to possess unique combinations of electroactive, coordinative, and optoelectronic properties and offer exceptional prospectives as materials for use in chemical power sources and OLEDs.…”
Section: Introductionmentioning
confidence: 99%
“…Like pyridylpyrroles, [8][9][10] they may display not only high electrical conductivity, but also the capability to form complexes of various chemical natures with better electronic and optoelectronic characteristics than uncomplexed polymers. Luminescent complexes of pyridylpyrroles with boron and zinc compounds have thus been proposed as an alternative to cyclometallated phenylpyridine ligands for use in organic light-emitting diode (OLED) materials, [8] while complexes of pyridylpyrroles with alcohols have been thoroughly explored as model compounds (analogous to pyridylindoles) for investigation of the natures of hydrogen bonds in such biologically important objects as DNA and RNA and for study of the mechanism of photoinduced mutagenesis through intermolecular excited state double proton transfer. [9,10] Polypyridines are known to possess unique combinations of electroactive, coordinative, and optoelectronic properties and offer exceptional prospectives as materials for use in chemical power sources and OLEDs.…”
Section: Introductionmentioning
confidence: 99%
“…[9] As Zn II with a closed shell is spectroscopically silent in essence, the luminescent properties of Zn II complexes can be easily tuned by the modification of the ligands. Meanwhile, Zn II complexes can have relatively flexible coordination numbers ranging from three-coordinate to six-coordinate depending on the structure of their ligands.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Among these known luminescent Zn complexes, the ligands are mainly benzothiazolates, [1] quinolinolates, [2] salicylideneaminates, [3] dipyrrin,…”
Section: Introductionmentioning
confidence: 99%
“…Heteroatom containing fluorophores develop partial charges due to internal charge transfer (ICT) and, interaction with charged groups can affect its energy. It has been reported that the metal ions can enhance or quench the fluorescence emission of pyridine containing compounds [57,58] depending on the strength interaction between ligand field potential and metal ion. In the absence of metal ions the fluorescence of ligand is probably quenched by the occurrence of PET process due to the presence of a lone pair on nitrogen atoms and vibrational relaxation of the molecule.…”
Section: Absorption and Emission Spectramentioning
confidence: 99%